Adultery: a novel - Coelho, Paulo (New York: Vintage Books, 2014)
A woman around her thirties begins to question the routine and predictability of her days. In everybody's eyes, she has a perfect life: a solid and stable marriage, a loving husband, sweet and well-behaved children and a job as a journalist she can't complain about. However, she can no longer bear the necessary effort to fake happiness when all she feels in life is an enormous apathy. All that changes when she encounters an ex-boyfriend from her adolescence. Jacob is now a successful politician and, during an interview, he ends up arousing something in her she hadn't felt for a long time: passion
International Bestseller
Keywords: Adultery -- Fiction; Married women -- Fiction; Novel; Psychological fiction